Method for enhancing surface conductivity of biochar, composite material of biochar loaded with transition metal and application of composite material

By constructing a highly conductive carbon layer on the cellulose surface, a cellulose biochar-based transition metal composite material was prepared, which solved the problem of insufficient conductivity of biochar, achieved efficient oxygen electrocatalytic performance, and had the advantages of low cost and high stability.

CN119640303AActive Publication Date: 2025-03-18NANJING AGRICULTURAL UNIVERSITY
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202510173790.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-18
Publication Date
2025-03-18
Estimated Expiration
2045-02-18

AI Technical Summary

Technical Problem

Biochar has low intrinsic conductivity, which limits its application in oxygen electrocatalysis.

Method used

By constructing a highly conductive carbon layer on the surface of cellulose, a cellulose biochar-based transition metal composite material is prepared to enhance its conductivity. The method includes impregnating cellulose in a solvent containing transition metal ions, performing hydrothermal reactions, forming a heteroatomic carbon layer, and obtaining a biochar composite material loaded with a transition metal by high temperature calcination and pickling treatment.

Benefits of technology

It realizes low-cost, high-activity and high-stability oxygen electrocatalyst, improves the conductivity and catalytic performance of biochar and has broad market prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119640303A_ABST
    Figure CN119640303A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of biochar surface modification, and discloses a method for enhancing biochar surface conductivity, a transition metal-loaded composite material and application thereof. In order to solve the problem of poor conductivity of biochar, lignocellulose or cellulose is soaked in a solvent containing transition metal ions and nitrogen / oxygen / phosphorus heteroatoms, a metal-heteroatom-cellulose complex precursor is formed through a hydrothermal reaction, then high-temperature calcination and acid pickling treatment are performed, and the metal-heteroatom-cellulose composite material is obtained. The composite material with a high-conductivity carbon layer and a stable transition metal nanoflower structure is prepared. According to the method, a metal-heteroatom doped carbon layer is formed on the surface of the biochar by utilizing the strong complexing action of transition metal, cellulose and a solvent, and the carbon layer has excellent interface electron transfer capability (Rct is equal to 1.671 omega). The obtained material has the advantages of high specific surface area, porous structure, excellent oxygen electrocatalytic activity and acid corrosion resistance stability, and can replace a noble metal catalyst to be applied to energy devices such as fuel cells.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of surface modification of cellulose biochar, and in particular to a method for enhancing the surface conductivity of biochar, a composite material of biochar loaded with transition metals and its application. Background Art

[0002] Developing efficient and sustainable energy conversion technologies is crucial to address global energy challenges. Among these technologies, oxygen electrocatalysis plays a key role in fuel cells and metal-air batteries. However, the performance of oxygen electrocatalysts is usually limited by their conductivity and stability.

[0003] Biochar, a material obtained by pyrolyzing biomass, is a promising material due to its high specific surface area, porosity, and environmental friendliness. Despite these advantages, the intrinsic conductivity of biochar is usually low, limiting its application in electrocatalysis. Therefore, enhancing the conductivity of biochar for oxygen electrocatalysts is a key research focus.

[0004] In recent years, a variety of strategies have been explored to improve the conductivity of biochar, including doping with heteroatoms and introducing metal nanoparticles. These modifications not only enhance conductivity but also introduce active sites that can improve catalytic performance.

[0005] As an innovative approach to enhance the conductivity of biochar and evaluate its application as an oxygen electrocatalyst, the modified biochar was systematically compared with existing catalysts to demonstrate its potential advantages in terms of activity and stability. Summary of the invention

[0006] In order to solve the problem of poor conductivity of biochar, the present invention prepares a conductive composite material that can maintain the original structure of cellulose by constructing a highly conductive carbon layer on the surface of cellulose, thereby preparing a low-cost oxygen electrocatalyst with high activity and high stability.

[0007] In order to achieve the above object, the present invention provides a method for enhancing the interfacial conductivity of biochar in a first aspect, the method comprising the following steps: (1) completely dissolving the transition metal ions in a solvent containing nitrogen, oxygen, and phosphorus heteroatoms, and immersing lignocellulose or cellulose in the solvent containing the transition metal ions to obtain a uniform dispersion; (2) transferring the dispersion to a hydrothermal reactor for a hydrothermal reaction. During the hydrothermal process, the transition metal ions act as a bridge and react with the hydroxyl groups on the surface of the cellulose and the heteroatom-containing functional groups in the solvent to form a complex. After the reaction is completed, centrifugation, washing, and drying are performed to obtain a precursor having a carbon layer loaded with heteroatoms and transition metal ions on the surface; (3) placing the precursor in a tube furnace and calcining it at a high temperature under the protection of nitrogen or an inert gas to obtain a calcined product.

[0008] (4) placing the calcined product in an acid solution and stirring it; after acid washing, centrifuging, washing, and drying it to obtain a cellulose biochar-based transition metal composite material.

[0009] In step (1), the lignocellulose or cellulose is derived from at least one of soybean straw, peanut straw, corn straw, cotton straw, etc. or cellulose extracted therefrom; and the lignocellulose or cellulose is sieved through a 60-mesh sieve.

[0010] The solid-liquid ratio of the lignocellulose / cellulose to the solvent containing nitrogen, oxygen and phosphorus heteroatoms is 1:3 to 1:60 g / mL.

[0011] The metal ions include but are not limited to Fe 3+ 、Zn 2+ 、Mo 5+ 、Ni 2+ 、Co 3+ One or more of the transition metal ions such as cellulose and iodine. Compared with other metals (such as main group metals Na⁺, Ca²⁺, Al³⁺), transition metals have unfilled d orbitals, variable oxidation states, and coordination diversity. They are more likely to complex with solvents containing heteroatoms (such as nitrogen, oxygen, phosphorus, etc.) to connect the heteroatom carbon layer formed by cellulose and solvent during the hydrothermal process.

[0012] The solvent containing nitrogen, oxygen and phosphorus heteroatoms is selected from at least one of formamide, citric acid aqueous solution, phytic acid and the like as a heteroatom source.

[0013] In step (2), the processing device for the hydrothermal / solvothermal reaction is a polytetrafluoroethylene reactor.

[0014] The temperature of the hydrothermal reaction is 120-200° C., and the time of the hydrothermal reaction is 6-24 h.

[0015] The number of washings with deionized water was 3 times.

[0016] The drying conditions are freeze drying or drying at 105°C.

[0017] In step (3), the inert gas includes one or a mixture of nitrogen, argon and helium; the flow rate of the nitrogen or inert gas is 100 to 500 mL / min.

[0018] The heating rate is 1-10°C / min.

[0019] The present invention controls the heat treatment temperature to be 900-1000°C. The high calcination temperature is conducive to the stable anchoring of metal particles. The heat treatment time is controlled to be 1-3 hours.

[0020] In step (4), the acid solution is an aqueous solution of an inorganic acid or an organic acid, preferably a sulfuric acid, hydrochloric acid or nitric acid solution with a concentration of 0.5 to 1 M.

[0021] The pickling treatment time is 24 hours; the pickling treatment temperature is room temperature to 80° C., preferably room temperature.

[0022] After the acid wash, wash with deionized water until neutral, and dry under freeze drying or drying at 105°C.

[0023] The second aspect of the present invention provides a cellulose biochar-loaded transition metal composite material prepared by the above method.

[0024] The third aspect of the present invention provides the use of the above-mentioned cellulose biochar-loaded transition metal composite material in electrocatalysis, especially as an oxygen electrocatalyst.

[0025] The present invention directly utilizes wood cellulose or cellulose as raw material, and prepares a transition metal composite material having a cellulose carbon framework (CF) through two steps of solvent heat and pyrolysis; The catalyst of the present invention is provided with a high specific surface area and a good porous carbon framework structure by cellulose carbon fiber (CF), and a layer of heteroatom-doped carbon layer is loaded on the surface to enhance the conductivity of biochar and can enhance the transfer of electrons on the interface and the carbon carrier; The cellulose biochar-based composite material of the present invention has simple preparation steps, a wide source of raw materials, and low cost. It has greater potential for large-scale production than traditional noble metal oxygen electrocatalysts and has broad market prospects in the application fields of proton exchange membrane fuel cells, zinc-air batteries, and other energy storage devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 Specific surface area (a) and pore size distribution (b) of the catalyst precursor n-Fe-NCF prepared in Example 1.

[0027] Figure 2 This is the X-ray electron spectrum (XPS) of the catalyst precursor n-Fe-NCF prepared in Example 1.

[0028] Figure 3 This is a scanning electron microscope (SEM) image of the catalyst precursor n-Fe-NCF prepared in Example 1.

[0029] Figure 4 This is the SEM image of the catalyst Fe-NCF prepared in Example 1.

[0030] Figure 5 This is a diagram verifying the theoretical calculation of the carbon layer formation mechanism on the surface of the Fe-NCF catalyst prepared in Example 1.

[0031] Figure 6 This is a high-resolution scanning transmission electron microscope (TEM) image of the catalyst Fe-NCF prepared in Example 1.

[0032] Figure 7 The catalyst Fe-NCF prepared in Example 1 was analyzed by Fourier transform infrared spectroscopy (FTIR).

[0033] Figure 8 Changes in element content of the catalyst Fe-NCF prepared in Example 1 before and after acid washing.

[0034] Fig. 9 This is the XPS spectrum of the catalyst Fe-NCF prepared in Example 1.

[0035] Fig.10 This is the X-ray derivative spectrum (XRD) of the catalyst Fe-NCF prepared in Example 1.

[0036] Fig.11 This is the Raman spectrum (Roman) of the catalyst Fe-NCF prepared in Example 1.

[0037] Fig.12 This is the linear sweep voltammetry (LSV) curve of the oxygen reduction reaction (ORR) of the catalyst Fe-NCF prepared in Example 1 under acidic conditions.

[0038] Fig.13 This is the impedance curve of the catalyst Fe-NCF prepared in Example 1.

[0039] Fig.14 This is the current variation curve (it) of the catalyst Fe-NCF prepared in Example 1.

[0040] Fig.15 This is the LSV curve of the catalyst Fe-NCF-1 prepared in Example 2 in the ORR test.

[0041] Fig.16 This is the impedance test curve of the catalyst Fe-NCF-1 prepared in Example 2.

[0042] Fig.17 This is the SEM image of the catalyst Mo-NCF prepared in Example 5.

[0043] Fig.18 This is the SEM image of the catalyst Mo, Fe-NCF prepared in Example 6.

[0044] Fig.19This is the SEM image of the catalyst NCF prepared in Comparative Example 1.

[0045] Fig. 20 This is the SEM image of the catalyst@NCF prepared in Comparative Example 2.

[0046] Fig.21 This is the SEM image of the catalyst CFC prepared in Comparative Example 3. DETAILED DESCRIPTION

[0047] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0048] The present invention provides a technical solution: a method for enhancing the surface conductivity of biochar, a composite material of biochar loaded with transition metals and application thereof. Example 1

[0049] In Example 1, a cellulose biochar-based transition metal composite material is prepared by the following method, the steps are as follows: Step (1), completely dissolving ferric chloride and zinc chloride in formamide, and immersing 0.5 g of cellulose in 30 mL of the solution to obtain a uniform cellulose dispersion; Step (2), transferring the cellulose dispersion obtained in step (1) to a polytetrafluoroethylene hydrothermal reactor, controlling the temperature of the hydrothermal reaction to be 180°C, the hydrothermal reaction time to be 12 h, and after the reaction is completed, centrifuging, washing with deionized water for 3 times, and freeze-drying at -48°C to obtain a precursor; Step (3), placing the precursor obtained in step (2) in a tube furnace, heating it to 900 ° C at a heating rate of 5 ° C / min and calcining it for 1 h in a 200 mL / min nitrogen atmosphere, to obtain a black solid, which is a biochar-based transition metal composite material precursor, recorded as catalyst precursor n-Fe-NCF.

[0050] Figure 1 a shows that the specific surface area of ​​the composite material is 510.27 m 2 / g, pore size distribution ( Figure 1 b) It can be seen that n-Fe-NCF has a porous structure. Figure 2 It can be seen that there are C, N, O and Fe elements on the surface of this material. The presence of C‒N bonds in the C 1s spectrum and the N 1s spectrum both confirm the successful doping of nitrogen in the carbon matrix, and the Fe 2p spectrum proves the successful introduction of Fe. Figure 3The SEM image shows that the nanoflowers cover the entire cellulose surface, covering up the fiber structure.

[0051] Step (4), the catalyst precursor n-Fe-NCF is further stirred under 0.5 M H2SO4 for 24 h, and then washed with deionized water to obtain Fe-NCF. After acid washing, the biochar-based transition metal composite catalyst Fe-NCF is obtained. This step corresponds to the method step (4). The unstable metal active sites are removed by acid washing, and the transition metal nanoflower structure stably loaded on the cellulose interface is retained. This structure is stable and resistant to acid corrosion.

[0052] Figure 4 This is the SEM image of Fe-NCF. It can be seen that after acid washing, the loosely bound nanoflowers are removed, and the surface of Fe-NCF is evenly distributed with nanoflowers that can stably load. From the cross-section and plane view of cellulose, it can be seen that the fiber is wrapped with a thick carbon layer, and the nanoflowers grow from the carbon layer. According to quantum mechanics theory calculation ( Figure 5 ) verified that the formation of the carbon layer is due to the following reasons: cellulose and formamide have abundant hydroxyl and carbonyl groups, which can provide sites for binding with iron ions ( Figure 5 a); The highest occupied molecular orbital (HOMO) energies of cellulose and formamide during the hydrothermal process are relatively high, indicating that their electrons are more easily transferred to iron ions during adsorption, so cellulose and formamide are more likely to coordinate with iron ions under this environment ( Figure 5 b); further analysis of the formamide and cellulose system ( Figure 5 c), the binding energy of formamide-Fe is -233.8 kcal / mol, and the binding force of cellulose-Fe is -334.2 kcal / mol. This indicates that the structure formed by the combination of iron with cellulose and formamide can exist stably. Subsequent pyrolysis can induce the movement of metal particles and promote the formation of active sites of nanoflowers on the surface of the carbon layer. Figure 6 TEM image of Fe-NCF, showing the metal active sites encapsulated within the carbon layer. Figure 7 In the Fourier transform infrared spectrum, the wavelength range is 900 ~ 650 cm −1 The intensity of the aromatic CH peak gradually increases, indicating that the aromatic structure is strengthened, proving that the surface of the biochar carrier tends to form an ordered carbon layer. This, together with the theoretical calculations, SEM and TEM results, proves that a carbon layer containing metals and heteroatoms has been formed on the surface of the cellulose-derived carbon. Figure 8 The comparison of the content of each element before and after pickling shows that about one-third of the iron element on the surface has been removed, indicating that the unstable active sites have been washed away under acidic conditions. Fig. 9From the XPS, we can see that the C 1s, N 1s and Fe 2p orbital peak fitting results in Fe-NCF are consistent with those in n-Fe-NCF, indicating that acid washing does not change the type of active sites, but only washes away the unstable active sites. Fig.10 It can be seen from the XRD that acid washing removes most of the unstable active metal components without changing the catalyst structure. Fig.11 The Raman spectra of Fe-NCF demonstrated that the active components were stably loaded.

[0053] The ORR performance test was carried out using a typical three-electrode system, with the catalyst Fe-NCF as the working electrode, the carbon rod as the counter electrode, and the saturated calomel electrode as the reference electrode in a 0.5 M H2SO4 electrolyte. Before the test, O2 was introduced into the electrolyte to reach a saturated state in order to reduce the effect of oxygen consumption in the solution during the ORR process. The linear sweep voltammetry curve (LSV) scan rate was 10.0 mV s ‒1 , the voltage range is 0~1.0 V vs. SCE.

[0054] from Fig.12 It can be seen that Fe-NCF has a good half-wave potential (0.743 V vs. RHE), showing good catalytic activity, and a half-wave potential comparable to that of commercial Pt / C. Fig.13 It can be seen from the impedance test curve that Fe-NCF has a low interfacial impedance of only 1.671 Ω, which proves that the catalyst interface has good electron transfer ability and the interfacial conductivity of the catalyst is enhanced.

[0055] In addition, from Fig.14 It can be seen that the current of Fe-NCF hardly decays within nearly 100 h, showing excellent stability, which also proves that Fe-NCF is resistant to acid corrosion. Example 2

[0056] The difference between Example 2 and Example 1 is that only the amount of cellulose added in step (1) is adjusted to 1.0 g, and 1.0 g of cellulose is immersed in 30 mL of formamide solution in which iron ions and zinc ions are dissolved to obtain a uniform cellulose dispersion. The remaining steps (2), (3), and (4) of Example 2 are the same as those of Example 1 to obtain the catalyst Fe-NCF-1.

[0057] The ORR performance of Fe-NCF-1 in an acidic electrolyte was tested according to the method of Example 1. The LSV curve of ORR is as follows: Fig.15As shown in the figure, the LSV curve shows that it has a good starting potential (0.764 V) and half-wave potential (0.677 V). The attenuation of performance is due to the increase in cellulose content, which leads to a decrease in the carbon layer loaded on the cellulose surface, proving that the surface carbon layer is the reason that affects the catalyst performance. Fig.16 As shown, the interfacial transfer impedance is 4.327 Ω. Although the reduction of the carbon layer on the cellulose surface leads to an increase in the interfacial impedance, it still exhibits a high charge transfer ability, which further proves that the carbon layer on the cellulose surface will significantly affect the conductivity of the biochar interface. Example 3

[0058] The difference between Example 3 and Example 1 is that only the type of solvent in step (1) is adjusted to citric acid aqueous solution, and the remaining steps (2)(3)(4) are the same as Example 1. Example 4

[0059] The difference between Example 4 and Example 1 is that only the type of solvent in step (1) is adjusted to phytic acid, and the remaining steps (2)(3)(4) are the same as Example 1. Example 5

[0060] The difference between Example 5 and Example 1 is that only the type of metal ions in step (1) is adjusted. In Example 5, zinc chloride and molybdenum chloride are added, and the remaining steps (2), (3), and (4) are the same as those in Example 1 to obtain the catalyst Mo-NCF. Fig.17 In the SEM image, it can be seen that there is a rough substance on the surface, which is the carbon layer formed by metal and formamide. Example 6

[0061] The difference between Example 6 and Example 1 is that only the type of metal ions in step (1) is adjusted. In Example 6, zinc chloride, ferric chloride and molybdenum chloride are added, and the remaining steps (2), (3) and (4) are the same as in Example 1 to obtain a catalyst Mo , Fe-NCF. Fig.18 The SEM image shows that there is a carbon layer on the surface of the sample that is clearly different from the cellulose-derived carbon, and nanoparticles are evenly dispersed on it. Example 7

[0062] The difference between Example 7 and Example 1 is that the type of biomass in step (1) is adjusted to lignocellulose, and the remaining steps (2), (3), and (4) are the same as Example 1. Comparative Example 1

[0063] The difference between Comparative Example 1 and Example 1 is that: in step (1), no metal ions are added, only 0.5 g of cellulose is uniformly dispersed in 30 mL of formamide solvent, and the other steps (2), (3), (4) are the same as those in Example 1, to obtain the catalyst NCF; according to Fig.19 The SEM images show that the surface of the cellulose-derived carbon is smoother than the carbon surface into which metal ions are introduced. This is because without metal ions as bridges, formamide alone cannot form a carbon layer on the cellulose surface. Comparative Example 2

[0064] The difference between Comparative Example 2 and Example 1 is that 0.5 g of cellulose in step (1) of Example 1 is directly mixed with zinc chloride and pyrolyzed at 900°C for 1 h to obtain @NCF. Fig. 20 From the SEM image, it can be observed that the fiber surface is severely broken and no carbon layer is formed on the fiber surface. This is because there is a lack of solvent thermal process, the solvent and metal cannot be complexed, and no carbon layer is formed on the cellulose surface. Comparative Example 3

[0065] The difference between Comparative Example 3 and Example 1 is that 0.5 g of cellulose in step (1) of Example 1 is directly pyrolyzed at 900°C for 1 h to obtain CFC. Fig.21 From the SEM image, it can be observed that the carbon surface collapsed by pyrolysis of biochar is relatively smooth, and obviously no new carbon layer is generated.

Claims

1. A method for enhancing the surface conductivity of biochar, characterized in that: The method comprises the following steps: (1) completely dissolving the transition metal ions in a solvent containing nitrogen, oxygen, and phosphorus atoms, and immersing the lignocellulose or cellulose in the solvent containing the metal ions to obtain a uniform dispersion; (2) transferring the dispersion to a hydrothermal reactor for hydrothermal / solvothermal reaction, and after the reaction is completed, centrifuging, washing, and drying to obtain a precursor having a carbon layer loaded with a layer of heteroatoms and transition metal ions on the surface; (3) placing the precursor in a tube furnace, introducing an inert gas as a protective gas, and maintaining the furnace at a high temperature for a period of time to obtain a calcined product; (4) placing the calcined product in an acid solution and stirring it; after acid washing, centrifuging, washing, and drying it to obtain a cellulose biochar-based transition metal composite material.

2. A method for enhancing the surface conductivity of biochar according to claim 1, characterized in that: The transition metal ions include Fe 3+ 、Zn 2+ 、Mo 5+ 、Ni 2+ 、Co 3+ One or more of the above.

3. A method for enhancing the surface conductivity of biochar according to claim 1, characterized in that: The solvent containing nitrogen, oxygen and phosphorus heteroatoms includes at least one of formamide and acetamide containing amide bonds, oxygen-containing citric acid aqueous solution and phosphorus-containing phytic acid.

4. The method for enhancing the surface conductivity of biochar according to claim 1, characterized in that: The wood cellulose or cellulose is derived from at least one of soybean straw, peanut straw, corn straw, cotton straw, etc. or cellulose extracted therefrom.

5. The method for enhancing the surface conductivity of biochar according to claim 1, characterized in that: The solid-liquid ratio of the lignocellulose / cellulose to the solvent containing nitrogen, oxygen and phosphorus heteroatoms is 1:3 to 1:60 g / mL.

6. The method for enhancing the surface conductivity of biochar according to claim 1, characterized in that: The processing device for the hydrothermal / solvothermal reaction is a polytetrafluoroethylene reactor, the temperature is controlled between 120-200°C, and the hydrothermal reaction time is controlled between 6-24 h.

7. A method for enhancing the surface conductivity of biochar according to claim 1, characterized in that: The acid solution is an aqueous solution of an inorganic acid or an organic acid, and the concentration of the aqueous solution is 0.5-1 M sulfuric acid, hydrochloric acid or nitric acid solution.

8. The method for enhancing the surface conductivity of biochar according to claim 1, characterized in that: The inert gas flow rate is 100-500 mL / min; the calcination temperature is 700-1000°C, the heating rate is 1-10°C / min, and the heat treatment time is controlled to be 1-3 h; the precursor washing condition is washing with deionized water for no less than three times, and the drying condition is freeze drying or drying at 105°C.

9. A biochar-based transition metal composite material prepared according to the method according to any one of claims 1 to 9.

10. Use of the biochar-based transition metal composite material according to claim 10 in electrocatalysis, lithium-ion batteries and electromagnetic compatibility.

Citation Information

Patent Citations

  • Carbon coated transition metal nano-composite material and preparation method and application thereof

    CN109304201A

  • Iron-nitrogen co-doped biochar, preparation method thereof and application of iron-nitrogen co-doped biochar in wastewater treatment

    CN115646525A

  • Heteroatom-doped carbon-coated metal catalyst and preparation method thereof

    CN115888785A

  • Plant fiber derived transition metal porous nitrogen-doped carbon catalyst as well as preparation method and application thereof

    CN116581306A

  • Preparation method of algae biochar-based catalyst and wastewater treatment method

    CN118022794A